Konsep Kerja Pengrajin Industri Sandal di Wedoro Waru Sidoarjo Perspektif Etika Bisnis Islam - Junaidy, Abdul Basith; Nadhifah, Nurul Asiya; Musyafa’ah, Nur Lailatul; Syafaq, Hammis (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2023)
This article discusses working according to sandal craftsmen in Wedoro village, Waru, Sidoarjo. The research was conducted in Wedoro village, Waru, Sidoarjo, East Java. Data collection through observation, interviews and documentation. The collected data was analyzed deductively using Islamic law. The study results concluded that most sandal craftsmen came from among the santri and were affiliated with the Nahdhatul Ulama religious organization. The concept of work they have is influenced by the religious teachings they acquire. They do five things at work, namely diligent and diligent, knowledgeable, innovating and understanding market needs, expanding networks and relationships, and being grateful. These five things are in accordance with the concept of Islamic law. In maqāṣid al-Sharia, work as a sandal craftsman corresponds to the objectives of hifẓ al-dīn, hifẓ al-nafs, hifẓ al-‘aql, hifẓ al-nasl and hifẓ al-māl.